2017
DOI: 10.1371/journal.pone.0170836
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of the Natural Insecticide, Decaleside Involves Sodium Pump Inhibition

Abstract: Decalesides are a new class of natural insecticides which are toxic to insects by contact via the tarsal gustatory chemosensilla. The symptoms of their toxicity to insects and the rapid knockdown effect suggest neurotoxic action, but the precise mode of action and the molecular targets for decaleside action are not known. We have presented experimental evidence for the involvement of sodium pump inhibition in the insecticidal action of decaleside in the cockroach and housefly. The knockdown effect of decalesid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
(43 reference statements)
0
21
0
Order By: Relevance
“…In 2012, (Rajashekar, Rao & Shivanandappa) described a new class of insecticide, namely, decalesides. These trisaccharides isolated from edible roots of Dendrocalamus hamiltonii turned out to have insecticidal activity targeting insects gustatory sites probably by sodium pump inhibition (Rajashekar & Shivanandappa, ). At the same time, as natural trisaccharides, they undergo rapid hydrolization in mammalian organisms, which makes these compounds safe for humans.…”
Section: Plant‐derived Substances Against Beetle Pests Of Stored Foodmentioning
confidence: 99%
“…In 2012, (Rajashekar, Rao & Shivanandappa) described a new class of insecticide, namely, decalesides. These trisaccharides isolated from edible roots of Dendrocalamus hamiltonii turned out to have insecticidal activity targeting insects gustatory sites probably by sodium pump inhibition (Rajashekar & Shivanandappa, ). At the same time, as natural trisaccharides, they undergo rapid hydrolization in mammalian organisms, which makes these compounds safe for humans.…”
Section: Plant‐derived Substances Against Beetle Pests Of Stored Foodmentioning
confidence: 99%
“…CEO includes many components such as flavonoids, alkaloids and monoterpenes, and has broad pharmacological efficacy (Osanloo, Sedaghat, Esmaeili, & Amani, 2018; Salim, 2017). Furthermore, the pharmacological effects of mentioned constituents are different, for example, the main site action of flavonoids is acetylcholinesterase (Perumalsamy, Jang, Kim, Kadarkarai, & Ahn, 2015), as well as alkaloids and monoterpenes target Na‐K‐ATPase or Na + and K + channels (Lucia, Zerba, & Masuh, 2013; Rajashekar & Shivanandappa, 2017). The differences between the pharmacological activities of CEO and its isolated compound, E may result from the synergistic or additive effects of the secondary compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, novel compounds are emerging that inhibit the Na + /K + -ATPase, including sanguinarine, an isoquinoline alkaloid from poppies (Mackraj et al, 2008), and palytoxin, a fatty alchohol from marine organisms (Rossini and Bigiani, 2011). Perhaps most relevant to the present study, trisaccharides (containing lactones) have been found in roots of Decalepis hamiltonii (Apocynaceae), which have strong insecticidal activity derived from inhibiting the Na + /K + -ATPase (Rajashekar and Shivanandappa, 2017).…”
Section: Asclepias Pachypodium and Novel Chemical Ecologymentioning
confidence: 91%
“…The sodium-potassium pump is a critical cellular enzyme occurring in all animal cells and is responsible for several primary functions, including the maintenance of cell resting potential. Recent work has found novel compounds in the Apocynaceae (e.g., trisaccharides), not traditionally included as cardiac glycosides, that nonetheless gain their toxicity from binding to Na + /K + -ATPase (Rajashekar and Shivanandappa, 2017). Despite the ubiquitous target site of cardiac glycosides in animal cells, hundreds of adapted insect species specialize on cardenolide-containing plants (Petschenka et al, 2013b;Bramer et al, 2015;Agrawal, 2017;Petschenka et al, 2017).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%